Role of surface hydrophilicity on MR relaxivity of PEG coated- gadolinium oxide nanoparticles. (1st January 2023) - Pranjali, Pranjali; Tripathi, Deepak Kumar; Chaturvedi, Anamika; Singh, Ranjan Kumar; Poluri, Krishna Mohan; Kumar, Dinesh; Guleria, Anupam
Abstract: The magnetic resonance (MR) contrast enhancement capabilities of gadolinium oxide nanoparticles (GONPs) have high dependency on its surface chemistry- as the solution properties such as colloidal stability and hydrodynamic diameter of nanoparticles which are prime regulatory parameter for MR relaxivity, are all governed by grafting density of surface material. However, the purification of synthesized surface coated nanoparticles, without compromising the surface properties, remains a major challenge. Among the various cleaning methods, dialysis is often used to remove the unwanted by-products produced during synthesis. However, the effect of dialysis time may significantly impact the surface properties and hence, the MR contrast properties of such nano-formulations. The aim of the present study is to evaluate the effect of dialysis time on surface chemistry and MR contrast enhancement properties of GONPs by comparing the proton relaxivity data. Ultra-small polyethylene glycol (PEG)-coated GONPs with an average particle diameter of 17 nm were synthesized using polyol method. The impact of dialysis time has been investigated systematically on the size distribution, hydrophilicity, magnetic properties, polymer grafting density and relaxometric properties of the as synthesized GONPs. A significant impact of dialysis time was observed on surface chemistry and hence, on the MR relaxivity of synthesized NPs. We evidenced a dramatic decrease in the proton relaxivities of GONPs with increase in dialysis time, which correlated well with the observed decrease in the grafting density of surface polymer. The results clearly indicate that the proton relaxivity of GONPs of similar size and same coating material depends on the surface coating thickness and hydrophilicity of the coating polymer. Overall, it is essential to optimize the accurate time duration of dialysis treatment as the prolonged dialysis may have negative effect on the relaxation times and hence on MR contrast enhancement properties of GONPs. This study is a strategic pathway to fine-tune the dialysis treatment of as-synthesized surface-capped GONPs for pre-eminent MR contrast imaging.